Synthesis and characterization of electrodeposited NiO thin film on electrode grade carbon plate for supercapacitor applications. (28th November 2017) - Sohail, Imran; Hussain, Zakir; Khan, Ahmad Nawaz; Yaqoob, Khurram
Abstract: The thin NiO film composing of submicron particles having optimum pseudo-capacitance is electrodeposited on electrode grade carbon plate through electrochemical strategy. In the first step Nickel oxide/hydroxide are deposited on the carbon substrate in 0.15 M Ni(NO3 )2 hexahydrate aqueous electrolyte. In the second step, deposited film is heat treated at 250 °C to completely transform any residual hydroxides to nickel oxide. The microstructures, composition and electrochemical characterization of the film is investigated in detail. The specific capacitance of NiO modified carbon electrode, calculated by Galvanostatic charge-discharge (GCD) test, showed a maximum specific capacitance of 950 F g −1 in 1 M KOH solution with electrodeposition of thin loosely packed NiO film having interconnected sphere-shaped submicron particles. Moreover, the electrodes showed good cyclic stability up to 500 cycles retaining more than 80% of original capacitance in cyclic charge discharge (GCD) test.